The Effects of the Incentive for Young and Female Employment Regulated By Law No. 6111 and Macroeconomic Variables on Employment, Informal Employment, and Income - Basbuga, Halit; Kitapci, Hakan (International Journal of Economics and Financial Issues, 2020)
This study examines the effects of macroeconomic variables and the Incentive for Young and Female Employment Regulated by Law No. 6111 in Turkey on employment, informal employment, and income. Electricity consumption (economic growth), USD/TRY exchange rate and inflation have been taken as the macroeconomic variables. Of the employment incentive policies implemented in Turkey, the employment incentive regulated by Law No. 6111 has also been used as a variable. Data have been taken monthly for the period 2012 through 2016. This study is significant because the data regarding the employment incentives implemented in Turkey are the actual data obtained from the Social Security Institution. As a result of the analysis, no significant impact of the Employment Incentive for Young and Female Employment regulated by Law No. 6111 and the examined macroeconomic variables was found on employment. The first lagged value of Inflation, one of the macroeconomic variables used in the study, had statistically significant impacts on the increase in informal employment. From macroeconomic variables, the USD/TRY exchange rate has a negative and relatively high impact. The increase in the exchange rate lowered revenue, as an expected outcome. Keywords: Employment, Informal Employment, Income, Employment Incentives, Electricity Consumption, Active Labour Market Policies JEL Classifications: D31, E24, J2 DOI: https://doi.org/10.32479/ijefi.10435